MODEL UNTUK PENETAPAN TARIF ZONA PARKIR (STUDI KASUS KOTA PADANG) - Asrizal Asrizal (Civil Engineering Departement, Andalas University, 2015)
Parking problem in Central Business District (CBD) of Padang City is the use of parking space on the roadside, especially on the Pasar Raya street that has exceeded capacities. Meanwhile, request of the parking space on the roads surrounding is still below the available capacity. To balance the demand and supply of the parking space in this area, a research is conducted to make a change of parking management through applying different tariff for different zones of parking. Tariff of parking in zone which have been identified, is calculated with equation of linear regression model which pursuant to probability of Willingness to Pay by service users. The antecedent survey which conducted to some respondent, indicate that factors such as tariff, distance, duration and accessibility, having an effect which enough to influence the probability of service user in choosing of location of parking. All factors did not correlate each other. Then, a research was conducted by collecting samples of data to 100 respondents through questioner survey and interview. The format of questioner was designed by using design of experiment